KETAHANAN AUS ABRASIF DARI BEBERAPA JENIS MODIFIKASI 13Cr BAJA TAHAN KARAT MARTENSITIK [The Wear Abrasion Resistant of Modifications of 13Cr Martensitic Stainless Steel] - Anwar, Moch. Syaiful (Jurnal Metalurgi, 2015)
The several components of steam turbine like the stator and rotor blade suffer from various kind of wear caused by solid particle erossion during turbine running. This paper presents the wear abrasion resistance of 13Cr martensitic stainless steel and its modifications. Four types of modification of 13Cr stainless steel is prepared with induction melting process and then cast into ingot molds. After casting process, each of ingot is conducted hot forging process followed by quenching and tempering process. Then the four type of stainless steel were conducted abrasion test against 120 SiC grinding paper, speed 100 rpm, load 100, 500 and 1000 g, and cycle 100, 300, 500, 700 and 1000 cycles. The results show that the higher wear abrasion resistant was found in the 13Cr3Mo3Ni martensitic stainless steel with weight loss of 43.13 mg/cm² and hardness of 47.5 HRc. The lower wear abrasion resistant was found in the 13Cr martensitic stainless steel with weight loss of 63.87 mg/cm² and hardness of 47.7 HRc.